Quinoxaline amino derivatives as potential EGFR-targeted therapeutics in breast cancer: computational exploration - Abitha H; D. Kumudha; Bhuvaneswari Sivaraman; M. K. Kathiravan (Journal of Applied Pharmaceutical Research, 2026)
Background: Despite resistance to current tyrosine kinase inhibitors, which makes the epidermal growth factor receptor (EGFR) a recognized therapeutic target in breast cancer, there is a need for novel inhibitors. Quinoxaline compounds are a promising scaffold for next-generation EGFR inhibitors and exhibit favorable pharmacological properties. Methodology: Ten new amino quinoxaline derivatives (QN1–QN10) were systematically developed and assessed by a comprehensive in silico approach. Molecular docking was conducted on the EGFR tyrosine kinase domain (PDB ID: 4HJO) utilizing Glide XP, with erlotinib serving as the reference ligand. Drug-likeness, oral bioavailability, and synthetic accessibility were evaluated using SwissADME, whereas pkCSM predicted ADMET characteristics. The most effective candidate was subsequently corroborated by 100 ns molecular dynamics (MD) simulations utilizing GROMACS 2021.1, succeeded by MM-GBSA binding free energy assessments. Results and Discussion: According to docking data, QN8 proved the most promising inhibitor. It showed stable hydrogen bonding with key EGFR hinge residues (MET769 and ASP831) and a high binding affinity (−9.305 kcal/mol), comparable to erlotinib (−9.501 kcal/mol). Consistent RMSD and RMSF profiles from MD simulations corroborated the structural stability of the QN8–EGFR complex. According to MM-GBSA analysis, the van der Waals, lipophilic, and electrostatic contributions were the main drivers of the favorable binding free energy (-73.63 kcal/mol). Pharmacokinetic predictions showed adequate ADMET properties and good oral absorption. Conclusion: This exhaustive computational analysis highlights amino quinoxaline derivatives as promising leads for developing breast cancer drugs, identifying QN8 as a strong EGFR inhibitor with stable binding dynamics and favorable drug-like properties.